The results of introduction of Scots pine Pinus sylvestris L. in Northen Kyrgyzstan - A. V. Ivanov (Сибирский лесной журнал, 2017)
The forests of Northern Kyrgyzstan are distinguished by poor species composition. Severe forest growing conditions, dry climate, vertical zoning, exposition of forests to the northern slopes, while the opposite slopes are treeless created a more or less tolerable conditions for the existence of only one species – Tien Shan spruce Picea schrenkiana Fisch. et Mey. Increase of productivity and stability, as well as strengthening protective properties of the spruce forests of Northern Kyrgyzstan is possible by the introduction of a tree species growing in other areas. For more than 80-year period in the region have been introduced about 120 different species of coniferous and deciduous trees. Many of them have second stage of introduction, noted by good growth, fruiting, and in some cases regeneration. The article summarizes the introduction of 83 years old Scots pine forest plantations in Northern Kyrgyzstan, growing in a variety of forest conditions. Forest inventory characteristic and an analysis of the growth in stem diameter is done. There is an estimation of the viability and prospects for the species in local conditions. Phenological observations completed. Regeneration of Scots pine and Tien Shan spruce in forest crops and out of its boundaries have been studied, which can lead to a species’ change in future. Pine in local conditions starts to occupy areas with severe forest growing conditions, and this confirms that the specie is acclimatized well and able to occupy areas, where Tien-Shan spruce can’t grow due to its bio-ecological features.